Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcvm.2022.1003442
|View full text |Cite
|
Sign up to set email alerts
|

Early ACEI/ARB use and in-hospital outcomes of acute myocardial infarction patients with systolic blood pressure <100 mmHg and undergoing percutaneous coronary intervention: Findings from the CCC-ACS project

Abstract: BackgroundFew studies have evaluated whether acute myocardial infarction (AMI) patients with relatively low blood pressure benefit from early ACEI/ARB use in the era of percutaneous coronary intervention (PCI).ObjectivesThis study evaluated the associations of ACEI/ARB use within 24 h of admission with in-hospital outcomes among AMI patients with SBP &lt; 100 mmHg and undergoing PCI.MethodsThis study was based on the Improving Care for Cardiovascular Disease in China-ACS project, a collaborative registry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…22 In patients with AMI, the cardioprotective mechanism of early administration of an ACEI/ARB could be attributed to reduction of RAAS activation and infarct size. 5 Moreover, we found a greater benefit for early administration of an ACEI/ARB in patients with obesity. Activation of the RAAS plays a central role in HTN, dyslipidemia, and insulin resistance in patients with obesity.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…22 In patients with AMI, the cardioprotective mechanism of early administration of an ACEI/ARB could be attributed to reduction of RAAS activation and infarct size. 5 Moreover, we found a greater benefit for early administration of an ACEI/ARB in patients with obesity. Activation of the RAAS plays a central role in HTN, dyslipidemia, and insulin resistance in patients with obesity.…”
Section: Discussionmentioning
confidence: 66%
“…Although ARB inhibits angiotensin II type 2 receptor, they are associated with lower levels of bradykinin and nitric oxide when compared to ACEI, and it has been found that ARB increases levels of angiotensin II to lead the upregulation of angiotensin‐converting enzyme 2, which has been demonstrated to provide protection for renal function 22 . In patients with AMI, the cardioprotective mechanism of early administration of an ACEI/ARB could be attributed to reduction of RAAS activation and infarct size 5 . Moreover, we found a greater benefit for early administration of an ACEI/ARB in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daisaku et al reported that beta-blocker treatment is still effective in the long-term outcomes of STEMI survivors without LV systolic dysfunction for secondary prevention after AMI [22]. The benefits of ACEI mainly appeared in higher-risk subgroups, but the survival benefit for patients in low-risk subgroups without these features is unclear [23,24]. In our study population, around 50% of the patients had an age below 65 years, and one-third were male (Table 1).…”
Section: Discussionmentioning
confidence: 99%